Effect of protein concentration and injection pressure in microinjection delivery of maltose binding protein into breast cancer cells - Lim, Shen Ni; Allaudin, Zeenathul Nazariah; Mohd Lila, Mohd Azmi; Othman, Abas Mazni; Othman, Fauziah (Universiti Putra Malaysia Press, 2011)
Microinjection is a powerful tool to deliver various substances, such as nucleic acids, proteins, peptides, RNA, and synthetic molecules into mammalian cells mechanically. Through microinjection, a controlled amount of protein can be delivered into the target cells to elucidate the specific functional effects in vitro. In this study, a series of protein microinjection optimization was performed in human breast cancer cells. The presence of Maltose Binding Protein (MBP) was microscopically monitored through indirect immunofluorescence assay. The optimization experimentation gave a high success rate when MBP protein was used at the minimum concentration of 1.5 mg/ml and at the injection pressures of 50 and 70 hPa. The average success rate of injections was 49.2±4.15% and 50.8±4.6%, while the average cell survivability was 50.98±4.67% and 49.72±5.48% at 50 and 70 hPa, respectively. The optimization of the MBP concentration and injection pressures successfully allowed an efficient delivery of precise protein dosage into breast cancer cells without any adverse effect. This microinjection optimization can be a practical guideline in any downstream applications of protein functional work.